Comparison of social capital's effect on consideration of suicide between urban and rural areas - Eiji Yamamura (Osaka University, Institute of Social and Economic Research (ISER), 2015)
An increasing number of works have addressed the socio-economic determinants of suicide. Social capital is a key factor in preventing suicide. However, little is known about the experience of suicide consideration using subjective values. From the viewpoint of suicide prevention, it is worth examining how people think of suicide. This paper attempts to examine the effect of social capital on suicide consideration based on individual-level data from Japan. Furthermore, the paper compares the effect of social capital between urban and non-urban areas. After controlling for various socio-economic factors, the major findings are that both individual-level social capital and social capital accumulated in one's place of residence reduce the probability that one will consider suicide. After dividing the sample into urban and non-urban residents, the effect of social capital in one's place of residence for urban residents is remarkably larger than for non-urban residents. In contrast, the effect of individual-level social capital disappears for urban residents, while the effect persists for non-urban residents. Overall, community-level social capital plays a more important role in deterring suicide for urban residents.
Keywords: 330